KAJIAN USAHA AGROINDUSTRI BERBAHAN BAKU NIRA AREN (CAP TIKUS DAN GULA AREN) DI DESA TOKIN KECAMATAN MOTOLING TIMUR - Sandi K. Wua; Theodora M. Katiandagho; Ribka M. Kumaat; Ellen G. Tangkere (Universitas Sam Ratulangi, 2014)
ABSTRACTMotoling regionis was an area with a lot of natural resources that can be processed to improve the usability and open jobs for the community. One of the natural resources that can be processed was palm trees that can be processed into Nira products such as alcoholic palm wine and palm sugar. More specifically in the village of the Tokin District of East Motoling it can be said that the treatment of alcoholic palm wine and palm sugar which has good potential for production and consumption habits of local communities to alcoholicpalm wine and palm sugar was exceptionally high.Collecting data of this study was obtained from the product processor farmers as many as 30 people consisted of 22 people from alcoholic palm wine and 8 people from palm sugar, by using a list of questions (questionnaire) as a tool, and secondary data of government agent related with this research.The research result showed that the difference between the revenue of alcoholic palm wine and palm sugar based on data from the real data without calculating the cost of labor and raw materials, was total ratio for alcoholic palm wine farmer acquired the R/C ratio of 21,36 and palm sugar with R/C ratio of 20,89. And the total profit for collecting trader alcoholic palm wine was Rp 10.298.805/month and for the palm sugaris was Rp 5.890.752/month. As for the alcoholic palm wine retailers was Rp1.380.000/month and for palm sugar retailer was Rp 990,000/month. It can be concluded that the business of processing and marketing of alcoholic palm wine collecting trader palm sugar.